Pengaruh Pemberian Pupuk Kotoran Sapi dan Dosis Pupuk Urea terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Usmadi; Husnul Khotimah (GEMA AGRO, 2025)
Pakcoy (Brassica rapa L.) is one of the horticultural commodities that belongs to the leafy vegetable category and is relatively easy to cultivate. This plant has a high economic value, diverse nutritional content, and a relatively short harvest time, making it an opportunity for farmers to meet market demand. However, pakcoy productivity is caused by suboptimal soil fertility due to nutrient deficiencies. One way to address this problem is to apply a combination of organic and inorganic fertilizers at the appropriate dosage. The aim of this research is to understand the interaction between the application of cow manure fertilizer and urea on the growth and yield of pakcoy plants. The experiment was conducted factorially using a Completely Randomized Design (CRD) with 2 factors and 3 replications. Factor I is the dose of cow manure fertilizer and factor II is the dose of urea fertilizer. The research results are: (1) The interaction of the treatment of cow manure fertilizer and doses of urea fertilizer showed a significant difference in the variable of plant height, but no significant difference in other variables. (2) The effect of cow manure fertilizer has a significant impact on the number of leaves, leaf area, fresh weight, dry weight, and productivity. (3) The effect of urea fertilizer doses has a significant impact on fresh weight, dry weight, and productivity.